Article Commentary: The 2019 Addiction Health Services Research Conference: Insights, Review, and Abstracts. Issue 4 (October 2019) - Garets, Mitchell; Archer, Shayla; Kitchens, Connie; Cochran, Gerald; Gordon, Adam J.
The 2019 Addiction Health Services Research (AHSR) Conference was held from October 16 to 18, 2019 in Park City, Utah. The conference was hosted by the Program for Addiction, Research, Clinical Care, Knowledge, and Advocacy within the Division of Epidemiology, Department of Internal Medicine at the University of Utah School of Medicine. AHSR is an annual conference to share discoveries, network with colleagues, and learn the most up-to-date research regarding how to identify, assess, and treat persons with addictions. This commentary contains 2019 AHSR specific goals and descriptions of content shared at this year's conference. Descriptions include information regarding pre-conference activities and conference plenaries, mentorship opportunities, and investigator awardees. Commentary also includes acknowledgments of those who assisted in making the 2019 AHSR Conference possible. Additionally, abstracts of the scientific research presented at the conference are included.